Hormone-Related and Drug-Induced Osteoporosis: A Cellular and Molecular Overview - Wang, Li-Ting; Chen, Li-Ru; Chen, Kuo-Hu (International journal of molecular sciences, 2023)
Osteoporosis resulting from an imbalance of bone turnover between resorption and formation is a critical health issue worldwide. Estrogen deficiency following a nature aging process is the leading cause of hormone-related osteoporosis for postmenopausal women, while glucocorticoid-induced osteoporosis remains the most common in drug-induced osteoporosis. Other medications and medical conditions related to secondary osteoporosis include proton pump inhibitors, hypogonadism, selective serotonin receptor inhibitors, chemotherapies, and medroxyprogesterone acetate. This review is a summary of the cellular and molecular mechanisms of bone turnover, the pathophysiology of osteoporosis, and their treatment. Nuclear factor-κβ ligand (RANKL) appears to be the critical uncoupling factor that enhances osteoclastogenesis. In contrast, osteoprotegerin (OPG) is a RANKL antagonist secreted by osteoblast lineage cells. Estrogen promotes apoptosis of osteoclasts and inhibits osteoclastogenesis by stimulating the production of OPG and reducing osteoclast differentiation after suppression of IL-1 and TNF, and subsequent M-CSF, RANKL, and IL-6 release. It can also activate the Wnt signaling pathway to increase osteogenesis, and upregulate BMP signaling to promote mesenchymal stem cell differentiation from pre-osteoblasts to osteoblasts rather than adipocytes. Estrogen deficiency leads to the uncoupling of bone resorption and formation; therefore, resulting in greater bone loss. Excessive glucocorticoids increase PPAR-2 production, upregulate the expression of Dickkopf-1 (DKK1) in osteoblasts, and inhibit the Wnt signaling pathway, thus decreasing osteoblast differentiation. They promote osteoclast survival by enhancing RANKL expression and inhibiting OPG expression. Appropriate estrogen supplement and avoiding excessive glucocorticoid use are deemed the primary treatment for hormone-related and glucocorticoid-induced osteoporosis. Additionally, current pharmacological treatment includes bisphosphonates, teriparatide (PTH), and RANKL inhibitors (such as denosumab). However, many detailed cellular and molecular mechanisms underlying osteoporosis seem complicated and unexplored and warrant further investigation.